PELATIHAN PEMBUATANDODOL PISANG SEBAGAI UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT - Putra, Reski Praja; Indrayani, Indrayani; Rahmah, Nur; Danial, Mohamad Ikbal Riski A.; Mustarin, Amirah (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
Panakkukang Village is located in Pallangga District, Gowa Regency, South Sulawesi. The village is approximately 13.2 km from the Department of Agricultural Technology, Faculty of Engineering, Makassar State University, with a travel time of approximately 26 minutes. The abundant natural resources in this area are rice and seasonal tropical fruits. Generally, tropical fruits are obtained only for personal consumption or some of the harvest is directly sold in the market as fresh. A farmer said that in Panakkukang Village, training on fruit processing has not been conducted. Generally, training is provided for farmers in cultivating rice fields to produce high rice yields. Raja bananas are one of the tropical fruits in this village. However, the utilization of raja bananas for processed products has not yet achieved optimal results. The purpose of this community service activity is to provide training to the community on the correct and good method of making raja banana dodol. The activity begins with the stages of observation, interviews, and discussions. Next, the delivery of material and counseling, demonstrations, mentoring, and assessment (evaluation). The ingredients used in this training consisted of plantains, coconut milk, glutinous rice flour, brown sugar, milk, and vanilla. These ingredients were then cooked over medium heat, stopping after the plantain dodol (rice cake) had been produced, characterized by a soft, non-sticky texture due to the oily surface from the coconut milk. Evaluation results indicated that participants had successfully produced plantain dodol independently. The plantain dodol they made was highly appreciated for its excellent sensory qualities.